68Ga-NOTA-RM26 PET/CT in the Evaluation of Breast Cancer: A Pilot Prospective Study. (September 2018) - Zang, Jie; Mao, Feng; Wang, Hao; Zhang, Jingjing; Liu, Qingxing; Peng, Li; Li, Fang; Lang, Lixin; Chen, Xiaoyuan; Zhu, Zhaohui
Abstract : Background: This prospective pilot study investigated the value of 68 Ga-NOTA-RM26, an antagonist targeting gastrin-releasing peptide receptor, in evaluation of breast cancer. Methods: Thirty-five women in suspicion of breast cancer based on mammography or ultrasonography were recruited with informed consent. They underwent PET/CT scans 30 minutes after intravenous injection of 68 Ga-NOTA-RM26 in a dose of 1.85 MBq (0.05 mCi) per kilogram body weight within 1 week before surgery. The 68 Ga-NOTA-RM26 uptake was correlated with the pathological and immunohistochemical findings. Results: 68 Ga-NOTA-RM26 positivity was found correlated with estrogen receptor (ER) expression ( P = 0.006) and menstrual status ( P = 0.019). In 34 patients diagnosed with breast cancer, the SUVmax was found significantly higher in the ER-positive breast cancer (4.97 ± 1.89) than in the ER-negative breast cancer (2.78 ± 0.65, P < 0.001). 68 Ga-NOTA-RM26 was also found accumulated in normal breast tissue, with the SUVmax significantly higher in patients at the secretory phase of menstrual cycle (2.27 ± 0.71) than in those at the nonsecretory phase (1.59 ± 0.49, P = 0.017) and postmenopause (1.43 ± 0.44, P = 0.002). If the secretory phase patients were excluded, the sensitivity, specificity, and accuracy for differentiation of breast cancer from breast tissue increased from 85.3%, 86.8%, and 86.1% to 100%, 90.9%, and 95.5%, respectively. Conclusions: This pilot study indicates that the diagnostic accuracy of 68 Ga-NOTA-RM26 PET/CT in breast cancer may correlate with ER expression and menstrual status of the patient. It may be better to avoid performing this examination during the menstrual secretory phase to reduce physiological uptake in normal breast tissue.